Determination of Trihalomethanes (THMs) in Drinking Water of Eastern Part of Bandar Abbas City and Feasibility of Removing with Ultrasonic Irradiation - roonak Khordedan; Aliakbar Azimi; Majid Baghdadi; Ali Zahedi (آب و فاضلاب, 2014)
Trihalomethanes are a group of compounds that can form when the chlorine used to disinfect drinking water reacts with naturally occurring organic matter. Trihalomethanes have been proven to be carcinogenic. The purpose of this study was to determine Trihalomethanes in drinking water of Eastern part of Bandar abbas city and to evaluate the feasibility of removing chloroform by ultrasonic irradiation. Sampling was performed from three stations located in the Eastern part of Bandar Abbas city and in the winter of 1389 and in the spring of 1390 (February and may). The maximum concentration of THMs was observed in the spring (119.3µgr/l) and the minimum concentration in the winter (68.7µgr/l). The concentration of THMs was less than of maximum acceptable concentration (200 µgr/l) established by Institute of Standards & Industrial Research of Iran.  Synthetic sample solutions containing chloroform were irradiated by ultrasound with intensity of 17.85 W/cm2.The results showed that the ultrasonic irradiation has the ability to remove Trihalomethans from aqueous solutions. After 8 minutes, 70% of chloroform was removed from sample solutions.